Pengaruh Penambahan Sukrosa Terhadap Mutu Organoleptik dari Selai Langsat - Yunus, Rafika (Gorontalo Agriculture Technology Journal, 2018)
Jam is food products with the consistency of gel or semi solid made of pulp fruit. fruit langsat abundant in particular season, so that need to be further processed to reduce the fruit removed due to damage. the addition of sucrose expected to increase the taste and texture of jam langsat. this study aims to know obtain the formulation of the addition of sucrose (sugar) corresponding to obtain jam good. this study was conducted in the laboratory technology agricultural University gorontalo and in the laboratory Polytechnic gorontalo. this research was conducted in the form of the design of randomized complete (RAL) consisting of 3 treatment and 3 times replicates. from the results of this study, based test organoleptic treatment preferred by panelists is treatment a2 (sugar 65%) with a score of color 3,9 (like), a sense of 4 (like), aroma 3,7 (like) and texture 4,1 (like)Â Keywords : langsat, jam, sucrose, test organoleptic